Revision of the Austro-Oriental shield-bug genus Axiagastus (Hemiptera: Heteroptera: Pentatomidae), with the description of five new species, and taxonomic notes on related genera - Salini, S.; Kment, Petr; Lemaître, Valérie A.; Webb, Michael D.; Roca-Cusachs, Marcos (Zootaxa, 2025)
The Austro-Oriental shield-bug genus Axiagastus Dallas, 1851 (Hemiptera: Heteroptera: Pentatomoidea: Pentatomidae: Pentatominae: Axiagastini) is revised and found to be a senior synonym of Indrapura China, 1928, syn. nov. The following Axiagastus species (including five new) are treated: A. cambelli Distant, 1911 (= Pentatoma marmoratum Montrouzier, 1855, syn. nov.), from Australia (Queensland), Papua New Guinea, Solomon Islands, Fiji, Samoa and Vanuatu; A. chandrashekarai Salini, Kment & Roca-Cusachs sp. nov., from Indonesia (Sulawesi); A. dubius Jensen-Haarup, 1937 from ?Singapore; A. klossi (China, 1928, Indrapura), comb. nov., from Indonesia (Sumatra); A. luteipes Salini & Roca-Cusachs sp. nov. from Myanmar; A. mitescens Distant, 1901, from China; A. prathapani Salini & Kment sp. nov., from India (Andaman and Nicobar Islands), Indonesia (Java, Sulawesi, Sumatra), Laos, Malaysia (Malaya, Sabah, Sarawak), and Singapore; A. rosmarus Dallas, 1851 (type species) from the Philippines; A. votypkai Salini & Kment sp. nov., from Indonesia (Papua), Papua New Guinea, Australia (Queensland), and A. yeshwanthi Salini, Kment & Webb sp. nov., from Cambodia, India, Japan (Ryukyus), Taiwan, Thailand and Vietnam. Lectotypes are designated for A. cambelli, A. rosmarus and Pentatoma marmoratum. We maintain the prevailing usage of Axiagastus cambelli and an application to the International Commission on Zoological Nomenclature is prepared to suppress its senior but unused synonym Pentatoma marmoratum. A checklist and key to the included species of Axiagastus are provided. In addition, the species status of Acesines breviceps Stål, 1876 is discussed and the following new subjective synonymy is proposed: Acesines breviceps = Acesines bambusana Distant, 1918, syn. nov. Comments on the collections and type material of William S. Dallas, Francis Walker, Jean X. H. Montrouzier and the Macleay Museum (now part of Chau Chak Wing Museum, University of Sydney) are provided.